1990
DOI: 10.1007/bf00307700
|View full text |Cite
|
Sign up to set email alerts
|

Unmyelinated fibers in sural nerve biopsies of chronic inflammatory demyelinating polyneuropathy

Abstract: Seven patients aged 29 to 76 years with various clinical subtypes of chronic inflammatory demyelinating polyneuropathy (CIDP) were investigated. Sural nerve biopsies were performed between 7 months and 19 years after onset of disease. Quantitative electron microscopy revealed involvement of primary unmyelinated fibers (UF) in all cases. When compared with age-matched controls from the literature and two controls of our own, there was an increase of degenerating primary UF in all cases, a definite decrease of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Our findings confirm recently published data demonstrating a reduction in CNF parameters in a cohort of 16 patients with CIDP 39. Our data are further supported by a previous study showing intraepidermal nerve fiber loss40 and unmyelinated nerve fiber degeneration in sural nerve biopsies41 of patients with CIDP. Patients with MMN showed the most marked reduction in CNF parameters, indicative of axonal loss.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings confirm recently published data demonstrating a reduction in CNF parameters in a cohort of 16 patients with CIDP 39. Our data are further supported by a previous study showing intraepidermal nerve fiber loss40 and unmyelinated nerve fiber degeneration in sural nerve biopsies41 of patients with CIDP. Patients with MMN showed the most marked reduction in CNF parameters, indicative of axonal loss.…”
Section: Discussionsupporting
confidence: 92%
“…Chronic inflammatory demyelinating polyneuropathy (CIDP) is an acquired inflammatory peripheral neuropathy of presumed autoimmune origin (Nobile‐Orazio , ). Although it is assumed that large myelinated nerve fibers constitute the primary target of the aberrant immune response in CIDP, biopsy studies have shown that small caliber sensory afferents are also frequently involved (Gibbels and Kentenich , ; Chiang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Large‐diameter axons are considered to be the major immunological target in CIDP. However, small‐diameter sensory fibers may be affected as well 15. Axonal degeneration occurs, to varying degrees, in lesions that are attributed primarily to demyelination 27.…”
mentioning
confidence: 99%